The Impact of the Banking Liquidity Shock on Banking Performance: An Applied Study at Bank of Baghdad (Entrepreneurship Journal for Finance and Business, 2025)
This research aims to analyze and evaluate the liquidity and banking performance indicators of the Bank of Baghdad for the period (2018–2023). Liquidity in Iraqi commercial banks is a crucial economic issue that impacts the financial and banking performance of the country, especially due to economic and political fluctuations that may hinder banks from providing sufficient funding for investment projects. This, in turn, negatively affects growth and production, leading to a decline in the financial performance of commercial banks. The research is based on the hypothesis that liquidity has a significant impact on banking performance. It adopts the deductive approach by combining both descriptive-analytical and quantitative methods. The study includes two variables: one independent and one dependent. The independent variable is the banking liquidity shock, while the dependent variables are banking performance, represented by the return on investment (ROI) and earnings per share (EPS). The researcher concluded that the Bank of Baghdad experienced very high liquidity ratios during the study period, indicating its ability to meet obligations and fulfill customer demands. This suggests that the bank enjoys strong financial performance and a solid credit position. However, profitability rates declined due to the bank’s efforts to balance liquidity and profitability.